Effect of Compound 21, a Selective Angiotensin II Type 2 Receptor Agonist, in a Murine Xenograft Model of Dupuytren Disease. Issue 5 (November 2017) - Chisholm, Jessica; Gareau, Alison J.; Byun, Stephanie; Paletz, Justin L.; Tang, David; Williams, Jason; LeVatte, Terry; Bezuhly, Michael
Abstract : Background: Although surgical excision and intralesional collagenase injection are mainstays in Dupuytren disease treatment, no effective medical therapy exists for recurrent disease. Compound 21, a selective agonist of the angiotensin II type 2 receptor, has been shown to protect against fibrosis in models of myocardial infarction and stroke. The authors investigated the potential use of compound 21 in the treatment of Dupuytren disease. Methods: Human dermal fibroblasts were treated in vitro with compound 21 and assessed for viability using a 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay, migration by means of scratch assay, and profibrotic gene transcription by means of quantitative reverse transcription polymerase chain reaction. Compound 21 effects in vivo were assessed using a xenograft model. Dupuytren disease cord specimens from patients undergoing open partial fasciectomy were divided into two segments. Segments were implanted under the dorsal skin of nude mouse pairs. Beginning on day 5, one mouse from each pair received daily intraperitoneal injections of compound 21 (10 μg/kg/day), and the other received vehicle. On day 10, segments were explanted and submitted for immunohistochemistry. Results: Human dermal fibroblasts treated with compound 21 displayed decreased migration and decreased gene expression of connective tissue growth factor, fibroblast specific protein-1, transforming growth factor-β1, Smad3, and Smad4. Dupuytren disease segments from compound 21–treated mice demonstrated significantly reduced alpha-smooth muscle actin and Ki67 staining, with increased density of CD31 + staining vessels. Conclusions: Compound 21 significantly decreases expression of profibrotic genes and decreases myofibroblast proliferation as indicated by reduced Ki67 and alpha-smooth muscle actin expression. These findings support compound 21 as a potential novel treatment modality for Dupuytren disease.